The Effect of Some Platelet Aggregating and Potential Thrombosis-Promoting Substances on the Development of Experimental Arterial Thrombosis - Hladovec, J (Thrombosis and Haemostasis, 1973)
A series of platelet aggregating or potentially thrombosis-promoting agents was administered intravenously 1 minute before the electric provocation of thrombosis in the carotid artery of the rat. Adenosine diphosphate, adrenaline, thrombin, ellagic acid, tannin, ε-aminocaproic acid and Trasylol were ineffective in shortening the time of thrombosis. On the contrary, most of these drugs showed some antithrombotic effect. Only 5-hydroxytryptamine definitely potentiated the process of thrombosis.